MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PAI BERVISI SETS (SCIENCE, ENVIRONMENT, TECHNOLOGI AND SOCIETY): DI KELAS VII-B SMP NEGERI 1 KWADUNGAN TAHUN PELAJARAN 2020/2021 - Suwartiningsih Suwartiningsih (Jurnal Paradigma, 2020)
Based on the results of classroom action research on PAI learning with the SETS vision (Science, Environment, Technology and Society) as an effort to improve the character of students who care about the environment that has been carried out by researchers in class VII B SMP Negeri 1 Kwadungan, it can be concluded as follows: 1) Character of participants environmental care students in PAI learning with SETS vision can increase in cycle I learning the character of students who care about the environment gains an average of 60% in the starting category, after improvements are made in cycle II the character of students cares about the environment increases by 16%, thus obtaining 76% with categories began to develop. Cycle III, the character of students who care about the environment gets 83% in the cultured category. 2) Student activities in PAI learning with SETS vision can increase in cycle I learning, student activities get 71% in the good category, after improvements are made in the second cycle, student activity increases 9%, so that 80% is obtained in good category, after repairs are made again in the third cycle of student activity gained an increase of 9%, so that obtained 89% in the very good category. 3) Research on PAI learning with SETS vision can improve student learning outcomes according to data analysis, it is known that the average value of evaluation increases in Cycle I: 74 Cycle II: 81 to 86 in Cycle III.